2020
DOI: 10.1001/amajethics.2020.888
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Wellness, and Native American Survivorship

Abstract: Native American women and femme-identifying individuals are twice as likely to be sexually assaulted as members of the general population. Given the high prevalence of violence experienced by members of this community, health care professionals and support staff must better understand social determinants of violence, barriers those experiencing violence face when seeking health care, and actions they can take to promote and implement change within systems that improve services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The Indian Law Resource Center (2020), a leading non-profit legal and advocacy resource organization for Indigenous people, found that four out of five American Indian and Alaska Native women experience violence, and more than one in two experience sexual violence (p. 1). These experiences of violence lead to significant trauma, substance use, depression, and other mental and physical health issues (Loerzel, 2020). Additionally, children of Indigenous women who experience intimate violence also experience high stress and anxiety, low self-esteem, and aggressive behaviors (Burnette & Cannon, 2014).…”
Section: Violence Against Indigenous Women: a Severe Yet Ignored Social Problemmentioning
confidence: 99%
“…The Indian Law Resource Center (2020), a leading non-profit legal and advocacy resource organization for Indigenous people, found that four out of five American Indian and Alaska Native women experience violence, and more than one in two experience sexual violence (p. 1). These experiences of violence lead to significant trauma, substance use, depression, and other mental and physical health issues (Loerzel, 2020). Additionally, children of Indigenous women who experience intimate violence also experience high stress and anxiety, low self-esteem, and aggressive behaviors (Burnette & Cannon, 2014).…”
Section: Violence Against Indigenous Women: a Severe Yet Ignored Social Problemmentioning
confidence: 99%